Relationship between aerobic and anaerobic power, and Special Judo Fitness Test (SJFT) in elite Iranian male judokas - Farzaneh Hesari, A.; Mirzaei, B.; Mahdavi Ortakand, S.; Rabienejad, A.; Nikolaidis, P. T. (Apunts Medicina de l'Esport, 2014)
The purpose of this study was to assess the relationship between aerobic and anaerobic power, and special judo fitness test in elite male judokas.